Analisis Pengaruh Persepsi dan Motivasi Wisatawan terhadap Minat Berkunjung ke Museum Wayang Jakarta - Laurentsa, Varren Graciela; Sarudin, Rendy (Jurnal Ilmiah Global Education, 2025)
This research was conducted at the Wayang Museum Jakarta with the aim of analyzing the influence of tourist perception and motivation variables on visiting interest. This study employed a descriptive quantitative approach, with data collected through the distribution of questionnaires to 100 respondents who had previously visited the museum. Respondents were selected using purposive sampling, and the collected data were analyzed with the assistance of SPSS software. The analysis results indicate that both perception and motivation variables have a simultaneous influence on visiting interest, with a contribution of (65.2%). The perception dimension includes both internal and external factors, while for motivation, physical drive and the desire to learn about culture are the most dominant aspects. The findings suggest the need for improved museum management strategies that are more relevant to current visitor expectations, including the optimization of digital media and the use of interactive technologies. This research is expected to provide insights for the sustainable development of cultural tourism destinations that align with the characteristics of today’s generation.